Activity Analysis of the Economic Entity and Digital Culture - E. B. Gerasimova (Мир новой экономики, 2019)
Subject. The modern economy is experiencing several crises related to the need for structural reforms and the solution to systemic problems. The solution to systemic and structural issues is influenced by the new business environment formed in the field of digital culture. It informs the participants of the national and international economy, dictates new requirements to economic entities, the results of their activities and the quality of business. New requirements of stakeholders influence the formation of the phenomenology of economic analysis in the era of digital culture.Purpose. The purpose of the research was the author’s development of phenomenology of economic analysis (analysis of economic entities) and the system of standardisation of economic analysis in the digital economy.Methodology. The author used methods of systems research (analysis and synthesis), comparative analysis, the method of analogies to solve the problems, and also the study of current economic literature and the use of structural analysis.Results. Based on the analysis, the author obtained the following results. Result 1: Diagnosis of the specific features (phenomena) of digital culture as a new business environment. Detection of the positive features and disadvantages of digitalisation of the economy. Result 2: Detection of the system of the phenomena forming phenomenology of the economic analysis which includes not only the phenomenon of the analysis, but also the phenomenon of the object and the subject of analytical activity; two last phenomena are modified under the influence of digital culture. Result 3: Detection of the boundaries of digitalisation of economic analysis: unification of methodological approaches to the analysis of normal operations of economic entities of different types (including households). Result 4: Detection of the mechanism of standardisation as a method of solving the problem of adaptation of methodological and methodical techniques of economic analysis to the activities of different economic entities, and a system of principles of standardisation of the analysis of economic entities. The author also considered the normative legal bases of standardisation of economic analysis in the Russian Federation. The author presented the model of system standardisation analysis activities of an economic entity that includes multiple contours, providing backwards and forward linkages between economic subject and interested in the analytical side of information in the process of formation and implementation of standards of evaluation.Conclusion. The development of the phenomenology of economic analysis is associated with the formation and improvement of the system of standardization of the analysis of economic entities that 1) meets the conditions of digitalization and innovation, 2) opens up great opportunities to improve the quality of economic entities, regardless of the specific scope of application of the results of analytical research.